Kerjasama Negara-Negara APEC dalam Mengatasi Ketimpangan Infrastruktur untuk Mencapai Pembangunan Internasional Pasca Pandemi Covid-19 - Nugroho, Naufal Hilmi; Aulia, Shafira; Dewantoro, Ridlo Bayu Alam; Sari, Deasy Silvya; Heryadi, R Dudy (Global Political Studies Journal, 2023)
During the COVID-19 pandemic, APEC member countries faced major challenges in achieving infrastructure development goals due to the COVID-19 pandemic impacting various aspects of people's lives and the economy, thus they looked for a way out. This article will use the theories of International Cooperation, International Development, and Dependencies. Issues will be discussed through qualitative research methods and analysis of secondary data sources. In overcoming this issue, APEC carried out the continuation of the plan of APEC Putrajaya Vision 2040, Experience Exchange, and the Belt Road Initiative. The cooperation that was carried out resulted in assistance in facilitating economic cooperation and regional integration. Even so, the cooperation that was actually carried out was planned even before the COVID-19 pandemic and was only carried out more actively to overcome the impact of the COVID-19 pandemic that was present. Keywords— APEC, Infrastructure inequality, International development